Digital Community Empowerment for Competitive Farmers in Marketing Farmer Products in Sigi Regency, Central Sulawesi, Indonesia - Mohammad Yasin; Idham (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This research examines digital empowerment and farmer competitiveness in Sigi Regency. The goal is to understand the digital empowerment process, the socio-cultural significance of farmers' digital activities, and their contribution to competitiveness. The approach used is qualitative interpretive with a cyber-phenomenology paradigm through photo elicitation and MDAP methods. The results indicate that digital empowerment encompasses economic, social, and cultural dimensions.